Hijacking the Cellular Mail: Exosome Mediated Differentiation of Mesenchymal Stem Cells - Raghuvaran Narayanan; Chun-Chieh Huang; Sriram Ravindran (Hindawi Limited, 2016)
Bone transplantation is one of the most widely performed clinical procedures. Consequently, bone regeneration using mesenchymal stem cells and tissue engineering strategies is one of the most widely researched fields in regenerative medicine. Recent scientific consensus indicates that a biomimetic approach is required to achieve proper regeneration of any tissue. Exosomes are nanovesicles secreted by cells that act as messengers that influence cell fate. Although exosomal function has been studied with respect to cancer and immunology, the role of exosomes as inducers of stem cell differentiation has not been explored. We hypothesized that exosomes can be used as biomimetic tools for regenerative medicine. In this study we have explored the use of cell-generated exosomes as tools to induce lineage specific differentiation of stem cells. Our results indicate that proosteogenic exosomes isolated from cell cultures can induce lineage specific differentiation of naïve MSCs in vitro and in vivo. Additionally, exosomes can also bind to matrix proteins such as type I collagen and fibronectin enabling them to be tethered to biomaterials. Overall, the results from this study show the potential of cell derived exosomes in bone regenerative medicine and opens up new avenues for future research.